EFFECT OF PRICE AND QUALITY OF SERVICE CUSTOMER LOYALTY (Study on Railway Passenger Blora Jaya PT. Kereta Api Indonesia (Persero) DAOP IV Semarang) - Fajar, Yulia Rossanda; Hermani, Agus; Budiatmo, Agung (Jurnal Ilmu Administrasi Bisnis, 2015)
Development and transportation services business competition is increasing rapidly. They compete in providing the best service to retain customers. This research was conducted at PT.Kereta Api Indonesia (Persero) Regional Operations IV Semarang object KA (train) Blora Jaya. Of user data KA Blora Jaya known of the fluctuations in the number of service users KA Blora Jaya and their number of user complaints Blora Jaya train services relating to facilities, infrastructure, and operational support services. As a company engaged in the field of services, PT.KAI (Persero) DAOP IV Semarang must provide good service to customers, good service offset by price according to what is given by PT. KAI (Persero) DAOP IV Semarang.This study aims to determine the effect of price (X1) and quality of service (X2) on customer loyalty (Y) railway services Blora Jaya. This type of research uses explanatory research with data collection method using interviews and data collection tools used questionnaires to a sample of 100 respondents KA customers Blora Jaya using purposive sampling method. Using analytical techniques validity, reliability, simple linear regression, multiple linear regression, t test and F test by means of SPSS 16.The results showed that the quality of service has a strong influence on customer loyalty by 49.4%, while the price is quite a strong effect on customer loyalty by 21,7%. This indicates that the variable quality of service to customer loyalty variable effect is higher than the variable price.Advice can be given to increase customer loyalty is to improve the quality of railway services Blora Jaya which is considered important by the service user, but still less attention from the company such as the availability of bins, seating capacity, the slow ticket officer in providing service that is the least number of counters that opened and have not been applied to tickets purchased online services.